Randomness, Integrability and Universality - AAVV (Il Colle di Galileo, 2024)
In spring 2022, the Galileo Galilei Institute for Theoretical Physics hosted a seven-week Workshop on ‘Randomness, Integrability and Universality’. The Workshop addressed a series of questions on exactly solvable models of statistical mechanics, having numerous ties and overlaps with various problems in random matrix models, probability, representation theory, and combinatorics. Much recent progress in these areas exploits the underlying notion of quantum integrability. Here we report on the scientific motivations and background of this activity and on its main outputs.